2003
DOI: 10.1103/physrevc.67.055209
|View full text |Cite
|
Sign up to set email alerts
|

Schematic model for QCD. I. Low energy meson states

Abstract: A simple model for QCD is presented, which is able to reproduce the meson spectrum at low energy. The model is a Lipkin type model for quarks coupled to gluons. The basic building blocks are pairs of quark-antiquarks coupled to a definite flavor and spin. These pairs are coupled to pairs of gluons with spin zero. The multiplicity problem, which dictates that a given experimental state can be described in various manners, is removed when a particle-mixing interaction is turned on. In this first paper of a serie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It appears that for some cases the high-j intruder orbital contributes with a 'quantized' alignment, where however the polarization contribution from the core is not taken into account. Also, in the mass A = 80 region, cases have been reported that do not fit at all into the pseudo-oscillator scheme, where the occupation of the unique parity orbital plays a role [170].…”
Section: Identical Bands: Hidden Symmetries or Accidental Cancellations?mentioning
confidence: 99%
“…It appears that for some cases the high-j intruder orbital contributes with a 'quantized' alignment, where however the polarization contribution from the core is not taken into account. Also, in the mass A = 80 region, cases have been reported that do not fit at all into the pseudo-oscillator scheme, where the occupation of the unique parity orbital plays a role [170].…”
Section: Identical Bands: Hidden Symmetries or Accidental Cancellations?mentioning
confidence: 99%
“…In [31], an effective algebraic Hamiltonian of QCD, for hadrons in general, was proposed and in [31][32][33] applied to describe hadron excitations, including gluons. Moreover, thermal excitations were considered in order to describe the physics of the Quark-Gluon Plasma, with quite a good agreement to the production of hadrons during the hadronization process.…”
Section: A Particular Application Of Nuclear Physics Methods To Parti...mentioning
confidence: 99%
“…In [34], the catastrophe theory [35] was applied to a pure system of gluons in order to describe the phase transition from a non-interactive gluon system to a system of interactive gluons, which should describe the real physical state. As a Hamiltonian, the one of [31,32] was used. It was found that the transition is of first order.…”
Section: A Particular Application Of Nuclear Physics Methods To Parti...mentioning
confidence: 99%
See 2 more Smart Citations